2022
DOI: 10.1108/jima-03-2022-0089
|View full text |Cite
|
Sign up to set email alerts
|

When love leads the way! Conceptualizing triangular theory of love and expectations-confirmation theory in Islamic banking

Abstract: Purpose This study aims to analyze the mediating effect of brand love (BRL) on the relationship between service quality and brand addiction (BRA) among Islamic banks. Past studies have noted that customer satisfaction as the primary means of studying customer behaviour needs to be reconsidered because even satisfied customer switch brands, and the dissatisfied customer have repurchasing intentions. Therefore, considering BRL and BRA can be a new way of studying customer behaviour in Islamic banking. Design/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 59 publications
(95 reference statements)
1
18
0
Order By: Relevance
“…The findings of the study suggest that consumer forgiveness is influenced by consumer religiosity through brand love. The results imply that when a consumer adheres to specific religious teachings that guide the consumer–brand relationship, they are more likely to forgive a brand with religious associations, facilitated by their emotional connection to the brand (Ismail, 2022). This sentiment is supported by religious teachings that emphasize the significance of love for fostering forgiveness (Fetscherin and Sampedro, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The findings of the study suggest that consumer forgiveness is influenced by consumer religiosity through brand love. The results imply that when a consumer adheres to specific religious teachings that guide the consumer–brand relationship, they are more likely to forgive a brand with religious associations, facilitated by their emotional connection to the brand (Ismail, 2022). This sentiment is supported by religious teachings that emphasize the significance of love for fostering forgiveness (Fetscherin and Sampedro, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Other scholars, such as Javed et al (2015), suggested that acceptance, commitment, respect, care and trust are indicators to measure love. The study by Ismail (2022) reported that indicators of love, such as commitment and trust, are vital in reducing customer switching behavior. Popp et al (2016) and Shuv-Ami et al (2020) highlighted that brand love implies the highest intensity and a long-lasting relationship with various interrelated affective, conative, cognitive and behavioral elements, rather than a specific, single, temporary love emotion.…”
Section: Brand Love (Brl)mentioning
confidence: 99%
See 3 more Smart Citations